Adenoid cystic carcinoma: immunohistochemistry and differential diagnosis, a case report - Mara Luana B. Severo; Caio César S. Barros; Lourival C. O. N. Rocha; Lucemário S. Macêdo; Márcia Cristina C. Miguel; Éricka Janine D. Silveira (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT A 52-year-old male patient complained of loss of sensitivity and pain in the maxilla. After examination, root canal treatment of tooth 12 was requested. Subsequently, there was a purplish increased volume of softened consistency in the area of vestibular attached gingiva of tooth 12. The anterior upper dental segment presented mobility. Incisional biopsy revealed malignant neoplasm of glandular epithelial origin, suggestive of solid adenoid cystic carcinoma (ACC). An immunohistochemical panel was performed, which confirmed the histopathological suspicion. Solid ACC may lead to diagnostic difficulties, since this lesion exhibits morphological features similar to other malignancies.